2011
DOI: 10.1007/s11431-011-4692-6
|View full text |Cite
|
Sign up to set email alerts
|

Atomic mobilities and diffusivities in Al alloys

Abstract: Knowledge of diffusivity is a prerequisite for understanding many scientific and technological disciplines. In this paper, firstly major experimental methods, which are employed to provide various diffusivity data, are briefly described. Secondly, the fundamentals of various computational methods, including first-principles method, embedded atomic method/molecular dynamic simulation, semi-empirical approaches, and phenomenological DICTRA technique, are demonstrated. Diffusion models recently developed for orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Self-, tracer- and chemical diffusion processes are important to understand mass transport in materials. A recent overview published by Du et al describes the different experimental techniques and different types of diffusion for aluminium alloys 41 . In particular, for self-diffusion measurements using capillary techniques and isotopes it was shown that ground-based experiments are severely affected by buoyancy effects and that microgravity experiments are able to provide buoyancy-free conditions 42 , 43 .…”
Section: Diffusion In Meltsmentioning
confidence: 99%
“…Self-, tracer- and chemical diffusion processes are important to understand mass transport in materials. A recent overview published by Du et al describes the different experimental techniques and different types of diffusion for aluminium alloys 41 . In particular, for self-diffusion measurements using capillary techniques and isotopes it was shown that ground-based experiments are severely affected by buoyancy effects and that microgravity experiments are able to provide buoyancy-free conditions 42 , 43 .…”
Section: Diffusion In Meltsmentioning
confidence: 99%
“…[16,17] The simulated morphology and coarsening of precipitation in Ni-Al alloys agrees well with experimental results. [18][19][20] The purpose of this paper is to better understand the effect of diffusivity on the c¢ phase microstructure, growth and coarsening kinetics, composition difference of Al in the c matrix, width of the c/c¢ interface and the mechanism of PSD using the diffuse-interface phase field model. To focus on the variable diffusion coefficient, strain induced by lattice mismatch was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, several atomic mobility databases for disordered alloys and alloys with magnetic ordering have been developed for different multicomponent alloys, e.g. Fe-, Ni-and Al-based alloys [11,12].…”
Section: Introductionmentioning
confidence: 99%